2014
DOI: 10.1039/c4ra04302b
|View full text |Cite
|
Sign up to set email alerts
|

Comparing extraction, synergism and separation of lanthanoids using acidic and neutral compounds in chloroform and one ionic liquid: is the latter always “better”?

Abstract: Five lanthanoid ions were extracted with 3-methyl-1-phenyl-4-(4-trifluoromethylbenzoyl)-pyrazol-5-one alone and in combination with partially substituted calix[4]arenes as synergistic agents using CHCl3 and one IL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 61 publications
2
70
0
Order By: Relevance
“…In our recent work, it was shown that La(III) was extracted with 3-methyl-1-phenyl-4-(4-trifluoromethylbenzoyl)-pyrazol-5-one in 1-butyl-3-methylimidazolium-bis(trifluoromethanesulfonyl)-imide, ([C1C4im][Tf2N]), as neutral LaL3 chelate but at the same time, the composition of the extracted species was established as LaL3·HL in CHCl3. 14 In ILs, it has been shown that lanthanoids maintain the usual coordination number they display in molecular diluents. 25 It is well known that hydrophobic ILs have higher water dissolving ability than conventional organic hydrophobic diluents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our recent work, it was shown that La(III) was extracted with 3-methyl-1-phenyl-4-(4-trifluoromethylbenzoyl)-pyrazol-5-one in 1-butyl-3-methylimidazolium-bis(trifluoromethanesulfonyl)-imide, ([C1C4im][Tf2N]), as neutral LaL3 chelate but at the same time, the composition of the extracted species was established as LaL3·HL in CHCl3. 14 In ILs, it has been shown that lanthanoids maintain the usual coordination number they display in molecular diluents. 25 It is well known that hydrophobic ILs have higher water dissolving ability than conventional organic hydrophobic diluents.…”
Section: Discussionmentioning
confidence: 99%
“…ii) Formation of self-adduct species LnL3·HL including one unprotonated acidic ligand. 11,14,31 Albinsson has established that in the organic phase (C6H6) at least two complexes exist, LnAa3 and the self-aduct LnAa3·HAa as well as for the lower lanthanoids (especially La) a second self-adduct, LnAa3(HAa)2 was supposed to be extracted with acetylacetone (HAa). 32 The solvent extraction behavior of all 4f-elements has been investigated in aqueous-benzene medium using 3-methyl-1-phenyl-4-benzoyl-5-pyrazolone (HP) and the composition of the species has been determined as LnP3·HP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…229 In general the substituent on the benzoyl ring in pyrazolone derivatives had low influence on the extraction efficiency (only 4-trifluoromethyl had a noticeable impact on the D values, Chart 2.43). 230 This topic has also been discussed in a recent review. …”
Section: Other Carbonylsmentioning
confidence: 99%